New and High Virulent Pathotypes of Sunflower Downy Mildew (Plasmopara halstedii) in Seven Countries in Europe - Rita Bán; Attila Kovács; Nisha Nisha; Zoltán Pálinkás; Mihály Zalai; Ahmed Ibrahim Alrashid Yousif; Katalin Körösi (Journal of Fungi, 2021)
Downy mildew of sunflower, caused by Plasmopara halstedii (Farl.) Berl. et de Toni, is a relevant disease of this crop. High virulent pathotypes have been identified in several countries, while there are few data on the spread of P. halstedii pathotypes in some important sunflower-growing areas of Europe. The goal of this study was to give up-to-date information on the pathotype structure of P. halstedii in Hungary and provide some actual data on the virulence phenotype of the pathogen for six European countries. Infected leaves of different sunflower hybrids and volunteers were collected in seven countries (Hungary, Bulgaria, Serbia, Turkey, Greece, Romania, and Italy) between 2012 and 2019. A universally accepted nomenclature was used with a standardized set of sunflower differential lines for pathotype characterization of isolates. The virulence pattern of the isolates was determined by a three-digit code (coded virulence formula, CVF). A total of 109 P. halstedii isolates were characterized. As a result of our survey, 18 new P. halstedii pathotypes were identified in Europe. Two out of the eighteen pathotypes were detected from the Asian part of Turkey. The detailed distribution of pathotypes in Hungary is also discussed.